PELATIHAN REGISTRASI AKUN DAN SUBMIT ARTIKEL BERBASIS OJS 3 - La Ode Sahidin; Andi Muh. Ruum Sya'baan; Fahruddin; Sri Suryana Dinar; La Ode Akhiri Zulzaman; Yustih Yasin (PT. CASA CENDEKIA MEDIA, 2024)
Students often face various challenges when trying to create or register an account on the Open Journal System (OJS), a platform used for managing scientific journals. One common issue is limited access, as some institutions don’t provide full access or clear guidance on how to use the platform. The registration process can also feel complicated, especially for first-timers, since the steps aren’t always straightforward. On top of that, technical issues like device compatibility or browser settings can make things even more frustrating. Institutional policies sometimes add another layer of difficulty, requiring students to meet extra conditions to sign up. The instructions provided on OJS are often incomplete or confusing, which doesn’t help either. Language barriers can be another obstacle, particularly for students who aren’t comfortable with the available languages on the platform. Lastly, slow or unstable internet connections can drag out the registration process, making it even harder to get started.